Legal Reasoning in Resolving Family and Inheritance Cases: A Theoretical and Practical Analysis - Lis Diana Ningsih; Ramdani Wahyu Sururie; Burhanuddin Burhanuddin (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, legal reasoning in family and inheritance cases should be guided by clear, consistent, and harmonized principles across the legal system. However, in reality, disputes often arise within a complex landscape involving overlapping norms, diverse interpretations, and variations in judicial practice. This research aims to analyze both the theoretical foundations and practical applications of legal reasoning used by judges and legal practitioners in resolving family and inheritance cases. Using a qualitative methodology, the study relies on doctrinal analysis, case studies, and comparative review of judicial decisions to understand how legal arguments are constructed and applied in real court settings. The findings show that although legal theory provides structured guidance, the resolution of family and inheritance disputes is largely influenced by contextual considerations such as cultural values, the coexistence of multiple legal systems, and the discretionary reasoning of judges. This dynamic interaction often leads to outcomes that balance normative frameworks with pragmatic socio-cultural realities.